Assessment of Sprint Parameters in Top Speed Interval in 100 m Sprint—A Pilot Study Under Field Conditions - Seidl, Thomas; Russomanno, Tiago Guedes; Stöckl, Michael; Lames, Martin (Frontiers in Sports and Active Living, 2021)
Improving performances in sprinting requires feedback on sprint parameters. Parameters from the top speed interval (TSI) are difficult to collect. Recent tracking technology provides positional data with high spatio-temporal resolution. This pilot study aims at obtaining general sprint parameters, parameters characterizing TSI and parameters during TSI (step length and time). In addition, we propose a method for obtaining the intra-cyclic speed (ICS) amplitude in TSI. We analyzed 32 100m-sprints of 7 male and 9 female athletes (18.9±2.8 years; 100m PB 10.55s-12.41s resp. 12.18s-13.31s). Spatio-temporal data was collected with a radio-based position detection system (RedFIR, Fraunhofer Institute, Germany). A general velocity curve was fitted to the overall speed curve (vbase), TSI (upper quintile of vbase values) was determined and a cosine term was added to vbase within TSI (vcycle) to capture the cyclic nature of speed. This allowed to derive TSI parameters including ICS amplitude from the fitted parameters of the cosine term. Results showed good approximation for vbase (error: 5.0±1.0%) and for vcycle (2.0±1.0%). The validation of TSI parameters resulted in acceptable RMSEs for means of speed (0.08m/s), for step time (0.004s) and for step length (0.03m). ICS amplitude showed a significant difference between males (mean: 1.41m/s) and females (mean: 0.71m/s) and correlations showed its independence from other sprint parameters. Gender comparisons for validation revealed the expected differences. This pilot study investigated the feasibility of estimating sprint parameters from high-quality tracking data. The proposed method is independent of the data source and allows to automatically obtain general sprint parameters and TSI parameters, including TSI amplitude assessed here for the first time.